2010
DOI: 10.1163/138577210x509606
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid as a Green Media for Rapid Synthesis of Optically Active Organosoluble Polyamides

Abstract: A variety of wholly aromatic organosoluble optically active polyamides (PAs) have been synthesized through polycondensation of a chiral diacid monomer and several aromatic diamines under microwave irradiation conditions. Polycondensations proceded in both ionic liquid and conventional organic solvent and compared results proved that ionic liquid in conjunction with triphenyl phosphite under microwave irradiation represented an advanced polyamidation agent from both environmental and economical viewpoints as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…[40,41] Mallakpour et al synthesized a series of chiral polyamides by using the combination of microwave irradiation and ionic liquids. [42][43][44] For instance, they synthesized chiral polyamides bearing l-phenylalanine and anthracenic units using ionic liquid/TPP or NMP/Py/TPP/CaCl 2 as a condensing agent with the assistance of a microwave-accelerated reaction system. [44] The results showed that ionic liquid can effectively absorb microwave radiation, resulting in faster polymerization rates in comparison to the polymerization in conventional solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Mallakpour et al synthesized a series of chiral polyamides by using the combination of microwave irradiation and ionic liquids. [42][43][44] For instance, they synthesized chiral polyamides bearing l-phenylalanine and anthracenic units using ionic liquid/TPP or NMP/Py/TPP/CaCl 2 as a condensing agent with the assistance of a microwave-accelerated reaction system. [44] The results showed that ionic liquid can effectively absorb microwave radiation, resulting in faster polymerization rates in comparison to the polymerization in conventional solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Recently, using of RTILs to form polymeric materials was found to take an enabling role in some fields of polymer chemistry and material science. [19][20][21][22][23] This includes immobilizing RTILs in solid devices and polymerizing RTILs with unsaturated bonds to give a special type of polyelectrolytes that carry an RTIL species in each of the repeating units. [24][25][26][27][28][29][30][31][32][33][34] In this work, a polymerizable RTIL, 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), and triethylamine (TEA) was synthesized by neutralization of AMPS and TEA, the co-polymeric gels of the RTIL with acrylamide (AAm) was synthesized, and it was found that the gels showed superabsorbency for both water and a variety of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most practical and widely accepted applications of chiral macromolecules is the use as chiral stationary phase (CSP) for high-performance liquid chromatography (HPLC) for the separation of racemic compounds (resolution). There are three types of chiral polymers used as CSP: biopolymers, polymers prepared by modification of naturally occurring polymer backbones such as polysaccharides and those having a fully synthetic structure [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The unique structures and the potential applications of these polymers have attracted researchers to develop various polymerization techniques. Owing to the importance of the green route for the synthesis of chiral extended polymers, in prolongation of our research [28][29][30][31][32][33], herein, we wish to describe a successful use of N -trimellitylimido-S-valine (1) to prepare optically active PAIs by the direct polycondensation with different diisocyanate using TBuAmBr an efficient, safe and environmentally benign green route by different catalysts. These results were compared with previous work with conventional solvents [34].…”
Section: Introductionmentioning
confidence: 99%